The Smart Coop: Revolutionizing Chicken Care with Automation - Kuhanraj, Kuhanraj A/L Kandarsamy; SUMAIYA BINTI MASHORI, SUMAIYA BINTI MASHORI (Progress in Engineering Application and Technology, 2024)
This study presents "The Smart Coop" to innovate chicken farmingin Malaysia by addressing challenges like resource scarcity andhigh operational costs. Using automated systems, it aims toimprove livestock conditions and implement machine learning foreco-friendly food production. Broiler farming in closed systemsfaces issues like increased costs, storm damage vulnerability, anddisease outbreaks, worsened by poor waste management. "TheSmart Coop" proposes autonomous monitoring of various factorsand integrating air filters for better environmental quality. Theproject seeks to create a smart chicken coop monitoring andcontrolling various aspects, incorporating eco-friendly elementslike air filters and rainwater collection, and evaluating the system'sreliability. The research methodology includes a literature review,case studies, and practical implementation with Arduino UNO.Performance testing involves temperature control, safetymeasures, and feeding automation. Findings indicate the smartcoop maintains optimal conditions for chicken welfare. Sensorsregulate temperature and ensure security, while automatedsystems promote healthy growth. The air filter eliminates odors,and the air cooler maintains a comfortable environment. While thecleaning system needs improvement, the coop overall meets itsobjectives. "The Smart Coop" shows potential in improvingchicken welfare, reducing environmental impact, and supportingsustainable poultry farming in Malaysia, with suggestions forfurther optimization